SDG 2.1 and SDG 2.2: Why open, transparent, and equitable trade is essential to ending hunger and malnutrition sustainably - Fan, Shenggen; Díaz-Bonilla, Eugenio; Cho, Emily EunYoung; Rue, Christopher (International Centre for Trade and Sustainable Development, 2018)
During the past years there have been several noteworthy global pledges on eliminating hunger, achieving food security and improved nutrition, and moving to environmentally sustainable patterns of production and consumption of food and agricultural goods. These pledges include the commitment to the Sustainable Development Goals (SDGs) in December 2015, followed by the entry into force of the historic Paris Agreement on climate change in November 2016, and the incremental advances at the World Trade Organization (WTO) during the 9th and 10th ministerial conferences in Bali in 2013 and in Nairobi in 2015, all of which represented important steps towards building a more supportive international system for the attainment of those objectives. However, as the limited results from the 11th Ministerial Conference in Buenos Aires in December 2017 suggest, much remains to be done for humanity to be able to achieve the SDGs by 2030. This paper will briefly consider the importance of trade in achieving the SDGs and transforming food systems. The paper also highlights some key policies that are critical to achieving these goals.